2020
DOI: 10.3889/oamjms.2020.4194
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Diabetes Mellitus Disease among High School Students in King Abdulaziz Military City, Tabuk, Saudi Arabia

Abstract: BACKGROUND: Saudi Arabia is considered to be one of the highest countries in the Middle East for the incidence of diabetes mellitus (DM). Data are lacking regarding knowledge and awareness about DM among school students in Saudi Arabia. AIM: The study aimed to assess the level of knowledge and awareness of DM among high school students within the military city, Tabuk, Saudi Arabia. METHODS: A descriptive type of cross-sectional study was conducted among 278 high school students applying a convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Male and young-age participants dominated a Jordanian study [20]. Overall, this study found that participants had limited knowledge about DM, which is similar to the results of previous studies in Saudi Arabia, Oman, and China, which indicated that school students had a general lack of understanding regarding DM [17,21,22]. This finding should be considered by policymakers and local authorities because, despite the development of information-dissemination channels such as the internet and social media, their levels of knowledge about common chronic diseases such as DM are still below expectations because there are not any school sessions or workshops on healthy eating and disease prevention.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Male and young-age participants dominated a Jordanian study [20]. Overall, this study found that participants had limited knowledge about DM, which is similar to the results of previous studies in Saudi Arabia, Oman, and China, which indicated that school students had a general lack of understanding regarding DM [17,21,22]. This finding should be considered by policymakers and local authorities because, despite the development of information-dissemination channels such as the internet and social media, their levels of knowledge about common chronic diseases such as DM are still below expectations because there are not any school sessions or workshops on healthy eating and disease prevention.…”
Section: Discussionsupporting
confidence: 83%
“…The present study aimed to assess knowledge and attitude levels about DM among school students in the west of Saudi Arabia. Although Saudi Arabia is one of the Middle Eastern nations with the highest incidences of DM, there is a lack of knowledge about DM among Saudi school students [17,19]. The sample we looked at represents students at different educational levels before entering a university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Alenazi et al (2020) mentioned relatively better (62.6%) knowledge scores in young school children regarding DM. 16 Quite interestingly, it was observed that females had significantly better knowledge regarding DM general knowledge, risk factors, signs and symptoms, control and management, complications, and total knowledge scores. A Chinese study reported inadequate knowledge of diabetes and its related factors among college students.…”
Section: Discussionmentioning
confidence: 95%
“…Alenazi ve ark. (2020) üniversite öğrencileri ile yaptığı araştırmada diyabet farkındalık düzeylerini alt boyutlara (Diyabetin tanılanması, diyabet sebebi, diyabet belirtileri, diyabet komplikasyonları) indirgemiş ve özellikle katılımcıların %80,6 sının diyabeti tanımlanmasında yetersiz olduğunu yani farkındalıklarının olmadığını bildirmiştir (31).…”
Section: İstatistiksel Analizunclassified